SENI LARASMADYA DESA WONOREJO KABUPATEN SUKOHARJO - Panggiyo Panggiyo (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2004)
Larasmadya contains religious values and promotes moral behavior  according to the Islamic religion, while at the same time presenting an  expression of art. For this reason, although there is a dichotomy  between the older and younger generations, the art of larasmadya in Wonorejo continues to exist.This art form originated from a  Kiyai, or religious leader, by the  name of Imam Suhada, who was an expert in Islam and supernatural  powers from the village of Wonorejo. The existence of larasmadya in  the village of Wonroejo is quite unique in that it has been passed down  from generation to generation within one family of descendants.Keywords: Larasmadya, eksistensi.